Evaluation of Antibacterial Properties of Carbon Sorbents - L G. Pyanova; V. T. Dolgikh; A. V. Sedanova; M. S. Delyagina; N. V. Kornienko; E. V. Naumkina; A. V. Lavrenov; A. V. Dubrovskaya (Антибиотики и Химиотерапия)
Background. Currently, the scientiﬁc search for alternative materials and methods for combating pathogens of infectious diseases is an important area of research. Carbon materials are one of the promising types of materials exhibiting antimicrobial and antifungal properties. The aim of the study is to investigate the antibacterial properties of modiﬁed carbon sorbents and initial modiﬁers in relation to some types of pathogenic microorganisms. The objects of the study were carbon sorbent samples before and after modiﬁcation with biologically active substances with antibacterial properties: salicylic acid, sulfosalicylic acid, tributyrin. The samples of carbon sorbents under study were obtained at the Center of New Chem- ical Technologies BIC. The following strains of gram-positive and gram-negative bacteria were used as experimental models: Staphylococcus aureus АТСС 25923; Pseudomonas aeruginosa АТСС 27853; Klebsiella pneumoniae 418; Esherichia coli АТСС 25922. Results. The highest sensitivity of gram-positive and gram-negative bacteria was established for a carbon sor- bent modiﬁed with tributyrin. The absence of growth of the studied test strains of microorganisms was observed after 2 hours of incubation of the «sample-microorganism» mixture.